Physicochemical and technological properties of pracaxi oil, cupuassu fat and palm stearin blends enzymatically interesterified for food applications - Salvador Reyes, Rebeca (2023)
Pure, blends and enzymatically interesterified blends in different proportions of pracaxi oil/cupuassu fat (PC) and pracaxi oil/palm stearin (PS) (w/w) (40:60, 50:50, 60:40 and 70:30), were characterized. Samples with the greatest food interest (70:30 w/w PC and PS) were characterized by X-ray diffraction, optical microscopy, and DSC. β crystalline form was reduced in interesterified blends. Crystals in the blends showed stable polymorphic forms, whereas interesterified blends showed a reduction in β crystalline form, and crystals in α form. PC and PS blends with pracaxi oil (70:30 w/w) showed the best atherogenicity (AI) 0.21 and 0.34 and thrombogenicity (TI) 0.38 and 0.55 indexes, respectively. Pracaxi oil has an oxidative stability of 2.32 h. Fats (cupuassu and palm stearin) has stability (3.60–6.51 h), and contributed to increase the oxidative stability of the blends. Pracaxi oil and cupuassu fat (40:60) reached oxidative stability of 3.85 h, while with palm stearin in the same proportion the stability increased to 4.34 h. Enzymatic interesterification increased the plastic range (SFC at temperatures up to 35 ◦C) of PC blends and reduced the SFC of PS blends. Interesterification caused a reduction in the consistency of the blends (p < 0.05), which shows the improvement in textural properties.